Muscle oxygenation during dynamic plantar flexion exercise: combining BOLD MRI with traditional physiological measurements. Issue 20 (24th October 2016) - Muller, Matthew D.; Li, Zhijun; Sica, Christopher T.; Luck, J. Carter; Gao, Zhaohui; Blaha, Cheryl A.; Cauffman, Aimee E.; Ross, Amanda J.; Winkler, Nathan J.R.; Herr, Michael D.; Brandt, Kristen; Wang, Jianli; et al.
Abstract: Blood‐oxygen‐level‐dependent magnetic resonance imaging (BOLD MRI) has the potential to quantify skeletal muscle oxygenation with high temporal and high spatial resolution. The purpose of this study was to characterize skeletal muscle BOLD responses during steady‐state plantar flexion exercise (i.e., during the brief rest periods between muscle contraction). We used three different imaging modalities (ultrasound of the popliteal artery, BOLD MRI, and near‐infrared spectroscopy [NIRS]) and two different exercise intensities (2 and 6 kg). Six healthy men underwent three separate protocols of dynamic plantar flexion exercise on separate days and acute physiological responses were measured. Ultrasound studies showed the percent change in popliteal velocity from baseline to the end of exercise was 151 ± 24% during 2 kg and 589 ± 145% during 6 kg. MRI studies showed an abrupt decrease in BOLD signal intensity at the onset of 2 kg exercise, indicating deoxygenation. The BOLD signal was further reduced during 6 kg exercise (compared to 2 kg) at 1 min (−4.3 ± 0.7 vs. −1.2 ± 0.4%, P < 0.001). Similarly, the change in the NIRS muscle oxygen saturation in the medial gastrocnemius was −11 ± 4% at 2 kg and −38 ± 11% with 6 kg ( P = 0.041). In conclusion, we demonstrate that BOLD signal intensity decreases during plantar flexion and this effect is augmented at higher exercise workloads. Abstract : In this human exercise physiology study, three different imaging modalities (ultrasound of the popliteal artery, blood‐oxygen‐level‐dependent magnetic resonance imaging, and near‐infrared spectroscopy) evaluated calf muscle microvascular physiology during exercise. Blood‐oxygen‐level‐dependent signal intensity in the gastrocnemius muscle decreased at higher workloads despite greater popliteal blood flow, indicating improved oxygen extraction.